Kampung Akuaponik: Pemodelan Teknologi Akuaponik Guna Meningkatkan Keterampilan dan Kemandirian Masyarakat Tempilang - Andri Kurniawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2014)
Utilization of narrow and unproductive land through fish farming is one way to increase land productivity. Aquaponic technology, which combines fish and vegetable farming with a recirculation system, is considered a simple but effective technology. This technology emphasizes land efficiency and the utilization of fish organic waste as fertilizer for the plants on it. The development of this technology can produce multiple products in one production cycle. Furthermore, this technology is able to increase the independence and productivity of the community so that it is indirectly expected to support their economy and welfare. KKN IX activities carried out by the Universitas Bangka Belitung (UBB) in Basun Village, Dam 3 Village, and Kelekak Kabung Village in Tempilang District are manifestations of the role of UBB's dharma of service to the community. The application of aquaponic technology is expected to bring new knowledge and skills to the community so that the optimization of non-productive land can be improved and able to produce something more useful and economically valuable.